PENYIMPANGAN PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA OUTSOURCING DARI KONTEKS UNDANG-UNDANG NOMOR 13 TAHUN 2003 - Totok Tumangkar (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2011)
To provide employment protection for a specific time or outsourcing manpower contracts, the provisions of Article 6 of Law No. 13 of 2003 on Manpower stated: